In Vitro Antioxidant Properties of Ficus exasperata Leaves and Its Effect on 1,2-dimethylhydrazine-Induced Liver Toxicity (CaJoST, 2025)
Ficus exasperata, locally referred to as the sandpaper plant belonging to the Moraceae family. This plant has been explored traditionally in the treatment of some ailments including anti-malarial, antibacterial, anti-diabetic, and lipid-lowering effects. This study investigates the in vitro antioxidant capacity of this plant. This study further investigates the influence of F. exasperata on the liver antioxidant status of healthy adult Wistar rats and 1,2-dimethylhydrazine-induced liver toxicity. A total of 24 Wistar rats (150-200g) were divided into four groups of 6 animals each. Group 1 was the control, Groups 2, 3, and 4 were given oral doses of methanol extracts of the leaf (each) at 125, 250, and 500mg/kg body weight respectively, for a total of twenty-eight days. For the 1,2-dimethylhydrazine-induced liver toxicity study, a total of 48 male Wistar rats were divided into 8 groups of 6 rats each with group 1 serving as the control, while groups 2-8 received either methanol extract of F. exasperata, 1,2-dimethyl hydrazine, or 5fluorouracil for 84days. At the end of the experimental period, biochemical assays were done, including, total protein, catalase, superoxide dismutase, glutathione peroxidase activities and MDA level. The results of rats treated with the plant extract only at different concentrations exhibited no changes. The DMH-induced toxicity shows clearly that the plant was able to mitigate the effect of the toxicant on the liver biomarkers. In vitro antioxidants study shows clearly that the extract could scavenge free radicals as seen in the scavenging activity of 1,1–diphenyl–2–picrylhydrazyl (DPPH) radical, Ferric Reducing Antioxidant Power (FRAP), nitric oxide, thiobarbituric acid reactive substance (TBARS), and reducing power. The results suggest that the extracts possess appreciable antioxidant activity and ameliorating capacity of toxicants which may be of high pharmaceutical importance.